Comparative Performance of Cross Breed Hampshire and Local Pigs in Field Condition in Zunheboto District - Chaurasia, Rakesh Kumar (Indian Journal of Hill Farming, 2017)
The present study was carried out in Akuluto block of Zunheboto district to study the comparative performance of crossbred Hampshire and local pigs at farmer’s field. Data obtained from the study shows that there was significant difference (P˂0.05) body weight gain per day was 176.79 ± 2.01 and 125.15± 1.96 for crossbred Hampshire and local pigs respectively. Average body weight at 15 months of age was 94.72 ± 0.66 and 60.70±1.02 kg respectively for crossbred Hampshire and local pigs which differed significantly (P˂0.05). Average weaning weight was 7.20 ± 0.39 and 4.5± 1.05 respectively for crossbred Hampshire and local pigs. Farrowing age and age at sexual maturity was 480.66 ±9.41, 520.88±2.45; 355.335±3.38, 410.55±3.37days respectively for crossbred Hampshire and local pigs which differed significantly (P˂0.05). Average Number of litter was7.44 ± 0.37 and 4.66±0.33 respectively for crossbred Hampshire and local pigs which differed significantly (P˂0.05). The result showed that cross bred pigs have a better productive and reproductive character and can be adapted successfully by the farming community.